(untitled) (Journal of EAHIL, 2024)
2024 has been another busy year for the Evidence-Based Information Special Interest Group (EBI-SIG). We had our annual meeting at the 2024 EAHIL Conference in Riga where we presented results from many of our projects. Since our last update in JEAHIL, we also ran two journal club meetings and two webinars. This report provides details of these activities.